Cleavage of single stranded oligonucleotides by EcoRI restriction endonuclease. - Bischofberger, N (1987)
The 31mer 5'-TCA ACG CTA GAA TTC GGA TCC ATC GCT TGG T, the complementary 33mer 5'-CCA AGC GAT GGA TCC GAA TTC TAG CGT TGA GAT, the 40mer 5'-GGC CAG GAT GGT GAA GAA TTC GAT CCG GTA CGT AGC TAA G, and the complementary 42mer 5'-TAC TTA GCT ACG TAC CGG ATC GAA TTC TTC ACC ATC CTG GCC were synthesized and their reactivity towards EcoRI was studied. It was found that the 31mer and the 40mer were cleaved at a comparable rate to the 31mer-33mer hybrid and the 40mer-42mer hybrid, respectively. The rate of cleavage of the 33mer and the 42mer was an order of magnitude lower. To rule out possible intermolecular duplex formation, the 33mer was immobilized on cellulose by ligation and labeled with alpha 32P-dCTP using Klenow fragment of E. coli DNA polymerase. EcoRI cleaved this immobilized oligomer into specific fragments.